Pengaruh Pemberian Buah Kurma pada Ibu Hamil Trimester III dengan Anemia terhadap Kadar Hemoglobin - Riaty, Zufrias; ursyam, Dian Eka (Poltekkes Kemenkes Padang, 2023)
Anemia is an important health problem throughout the world. Approximately 51% of pregnant women suffer from anemia twice as often as non-pregnant women. Anemia in pregnancy is those who have Hb levels <11 gr% in the first trimester and third trimester and Hb levels <10.50 gr%. Dates are a food that contains high energy with an ideal composition, containing carbohydrates, tryptophan, omega-3, vitamin C, vitamin B6, Ca2+,Zn, and Mg. Research design with Quasi Experimental non-Equivalent control group design. The research sample size was 15 pregnant women.The research results showed that the hemoglobin level before giving dates was the lowest 9 gr/dL and the highest 15 gr/dL. And the average is 10 gr/dL. Hemoglobin level values after giving dates were the lowest, 11.5 gr/dL, the lowest and the highest, 16 gr/dL. And the average is 13 gr/dL. The Shapiro-Wilk value is 0.039 < 0.05, so the data is not normal. Because the data was not normal, the test was continued with the non-parametric Wilcoxon test. Positive ranks 15 means that all 15 samples experienced an increase in HB from the previous value to the next value. Meanwhile, mean rank 8 is the average increase in HB. The positive number is 120,Ties 0 means there is no similarity in HB values before and after. This research concludes that there is an effect of giving dates on increasing hemoglobin levels in pregnant women.